IMPROVING CORPORATE SUSTAINABILITY THROUGH IMPLEMENTING GREEN ACCOUNTING AND MATERIAL FLOW COST ACCOUNTING - Irma Tripalupi, Ramdhani; Afrianti, Rika; Asma' Binti Mohd Rosdi, Siti; Sakinah, Gina; Zaky, Muhammad (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2026)
This study aims to analyse how the implementation of green accounting and material flow cost accounting (MFCA) can enhance corporate sustainability in mining companies listed on the Indonesian Sharia Stock Index (ISSI). Green accounting is measured through the PROPER program, while MFCA is proxied by factory area and production output. The study uses a quantitative approach and purposive sampling from companies listed on the ISSI for the 2021-2023 period. The results show that green accounting does not have a significant effect on improving corporate sustainability. MFCA, measured by factory area, shows no significant relationship in improving corporate sustainability. In contrast, MFCA, proxied by production output, has a significant positive effect on corporate sustainability. Meanwhile, green accounting and MFCA have a substantial impact on improving corporate sustainability. The study's results indicate that the simultaneous approach is more effective at supporting sustainability. The synergy between green accounting and MFCA helps companies formulate sustainable business strategies by ensuring compliance, thereby driving innovation and competitive advantage through transparency, environmental accountability, resource efficiency, and waste reduction.